HIV RNA Screening Reduces Integrase Strand Transfer Inhibitor Resistance Risk in Persons Receiving Long-Acting Cabotegravir for HIV Prevention. (14th October 2022) - Eshleman, Susan H; Fogel, Jessica M; Halvas, Elias K; Piwowar-Manning, Estelle; Marzinke, Mark A; Kofron, Ryan; Wang, Zhe; Mellors, John; McCauley, Marybeth; Rinehart, Alex R; St Clair, Marty; Adeyeye, Adeola; et al.
Abstract: Background: The HPTN 083 trial demonstrated that long-acting cabotegravir (CAB-LA) was superior to tenofovir-disoproxil fumarate/emtricitabine for human immunodeficiency virus (HIV) preexposure prophylaxis (PrEP). Integrase strand transfer inhibitor (INSTI) resistance-associated mutations (RAMs) were detected in some participants with HIV infection. We used a low viral load INSTI genotyping assay to evaluate the timing of emergence of INSTI RAMs and assessed whether HIV screening with a sensitive RNA assay would have detected HIV infection before INSTI resistance emerged. Methods: Single-genome sequencing to detect INSTI RAMs was performed for samples with viral loads <500 copies/mL from 5 participants with previously identified INSTI RAMs and 2 with no prior genotyping results. Results: Major INSTI RAMs were detected in all 7 cases. HIV RNA testing identified infection before major INSTI RAMs emerged in 4 cases and before additional major INSTI RAMs accumulated in 1 case. Most INSTI RAMs were detected early when the viral load was low and CAB concentration was high. Conclusions: When using CAB-LA PrEP, earlier detection of HIV infection with a sensitive RNA assay may allow for earlier treatment initiation with the potential to reduce INSTI resistance risk. Further studies are needed to evaluate the value and feasibility of HIV RNA testing with CAB-LA PrEP. Abstract : With cabotegravir PrEP failure or inadvertent use in undiagnosed​ infection, integrase strand transfer inhibitor (INSTI) resistance mutations often emerged before rapid and antigen/antibody tests were reactive. Use of an RNA assay to identify infections may reduce INSTI resistance risk.